THE BENEFITS OF SOMALIA’S IAEA MEMBERSHIP: ADVANCING DEVELOPMENT THROUGH NUCLEAR TECHNOLOGY - Ulusow, Ayub Hassan; Ali, Hussein Abdullahi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Somalia’s membership in the International Atomic Energy Agency (IAEA) marks a pivotal step in its development journey. As the IAEA promotes the peaceful use of nuclear technology, Somalia stands to benefit significantly in sectors such as agriculture, health, energy, and environmental management. This review explores the potential contributions of IAEA membership to Somalia’s development, focusing on nuclear technology applications in various sectors, and provides real-time data on the ongoing projects and collaborations. The paper also highlights challenges Somalia might face in fully utilizing IAEA support and suggests strategies for optimizing the country's engagement with the agency.